2006
DOI: 10.1301/nr.2006.jul.301-312
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Therapy in Idiopathic Nephrolithiasis

Abstract: Like other diseases striking predominantly the affluent societies, idiopathic nephrolithiasis is increasing in rich countries and appears to be closely related to dietary habits. In this review we summarize the latest evidence about the efficacy of dietary treatment for idiopathic calcium and uric acid stones, dealing especially with its effect on the urinary stone risk factors, stone recurrences, and clinical limitations. After a short introduction on epidemiology and pathogenesis, we review the role of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 44 publications
(60 reference statements)
0
20
1
Order By: Relevance
“…Increased intake requirements may be required during periods of increased insensible water loss. Regarding fluids other than water, reports suggest that fluids that increase urinary pH and citrate excretion such as orange juice, lemonade, and black currant juice, as well as those that increase urinary volume such as coffee, tea, beer, and wine, reduce the risk of calcium stone formation 43 . Conversely, grapefruit juices seem to increase the risk of calcium-based stones 43,44 .…”
Section: Medical Managementmentioning
confidence: 99%
“…Increased intake requirements may be required during periods of increased insensible water loss. Regarding fluids other than water, reports suggest that fluids that increase urinary pH and citrate excretion such as orange juice, lemonade, and black currant juice, as well as those that increase urinary volume such as coffee, tea, beer, and wine, reduce the risk of calcium stone formation 43 . Conversely, grapefruit juices seem to increase the risk of calcium-based stones 43,44 .…”
Section: Medical Managementmentioning
confidence: 99%
“…Sodium intake has a major role as a risk factor for stone formation in view of the fact that high urinary sodium excretion has been repeatedly associated with hypercalciuria in adult and pediatric populations [90, 91]. Sakhaee et al have shown that sodium loading in healthy adult subjects increases urinary pH and the relative supersaturation ratios of brushite and monosodium urate but reduces urinary citrate excretion and serum bicarbonate levels [92].…”
Section: Differences In Epidemiologymentioning
confidence: 99%
“…Apart from low urinary volumes ( 2 L/day) and low urinary flow rates other risk factors for kidney stones exist. (Borghi et al, 2006).…”
Section: Dehydrationmentioning
confidence: 99%